Benefits and Barriers: An Exploratory Study of Nephrology Social Work Field Education - Browne, PhD, MSW, NSW-C, Teri; Pooler, PhD, MSSW, David (The Journal of Nephrology Social Work, 2012)
An important aspect of the profession of social work is the requirement of at least 900 hours of a “field placement” internship for all masters-level social worker (MSW) students as part of their education in accredited U.S. schools of social work (Council of Social Work Education, 2008). The goals of this project are to increase the number of South Carolina dialysis units that offer MSW students field placement opportunities, and to explore professional and personal benefits and barriers for dialysis social workers assuming the role of field educators. Ten social workers participated in the project’s interviews about the benefits of and barriers to being an MSW field educator. Ultimately, 6 social workers contracted with the University of South Carolina to accept students for field placement in dialysis units, and 2 students completed their field placement in dialysis units for the academic year 2010–2011. The MSW-level social workers reported several barriers to being field educators: their relationships with the USC College of Social Work, organizational climate, organizational functioning, social work caseload and tasks, professional identity, and general concerns about students. Social workers also identified possible areas benefiting from being social work field educators: organizational climate, patient care, workload, professional obligation, intrinsic rewards, and the fact that a dialysis unit could be a rich learning environment for MSW students.